Knowledge and attitude on maternal health care among rural-to-urban migrant women in Shanghai, China - Gao Yi; Kulane Asli; Zhao Qi; Xu Biao (BMC, 2009)
Abstract Background In China, with the urbanization, women migrated from rural to big cities presented much higher maternal mortality rates than local residents. Health knowledge is one of the key factors enabling women to be aware of their rights and health status in order to seek appropriate health services. This study aims to assess the knowledge and attitude on maternal health care and the contributing factors to being knowledgeable among rural-to-urban migrant women in Shanghai. Methods A cross-sectional study was conducted in a district center hospital in Shanghai where migrants gathered. Totally 475 rural-to-urban migrant pregnant women were interviewed and completed the self-administered questionnaire after obtaining informed consent. Results The mean score of knowledge on maternal health care was 8.28 out of 12. However, only 36.6% women had attended the required 5 antenatal checks, and 58.3% of the subjects thought financial constrains being the main reason for not attending antenatal care. It was found that higher level of education (OR = 3.3, 95%CI: 1.8-3.8), husbands' Shanghai residence (OR = 4.0, 95%CI: 1.3-12.1) and better family income (OR = 3.3, 95%CI: 1.4-8.2) were associated with better knowledge. Conclusions Rural-to-urban migrant women's unawareness of maternal health service, together with their vulnerable living status, influences their utilization of maternal health care. Tailored maternal health education and accessible services are in demands for this population.